2020
DOI: 10.3390/ijerph17207544
|View full text |Cite
|
Sign up to set email alerts
|

Review of Organizational Health Literacy Practice at Health Care Centers: Outcomes, Barriers and Facilitators

Abstract: The term organizational health literacy (OHL) is a new concept that emerged to address the challenge of predominantly in patients with limited health literacy (HL). There is no consensus on how OHL can improve HL activities and health outcomes in healthcare organizations. In this study, a systematic review of the literature was conducted to understand the evidence for the effectiveness of OHL and its health outcome, and the facilitators and barriers that influence the implementation of OHL. A literature search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…The results of a meta-analysis study showed that there was a correlation between health literacy and quality of life [16]. Some results indicated that poor health literacy was related to poor quality of life, and this relationship could be due to reduced access to medical care, increased stress due to the challenges of daily living, poor selfmanagement, and reduced self-efficacy [16][17][18][19]. On the other hand, because health literacy was affected by many factors (including factors of individual, social, and cultural); any society has reported different results [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The results of a meta-analysis study showed that there was a correlation between health literacy and quality of life [16]. Some results indicated that poor health literacy was related to poor quality of life, and this relationship could be due to reduced access to medical care, increased stress due to the challenges of daily living, poor selfmanagement, and reduced self-efficacy [16][17][18][19]. On the other hand, because health literacy was affected by many factors (including factors of individual, social, and cultural); any society has reported different results [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This term was first published in 1974 at the health education conference, which discussed the determinants of social health that affect mass communication, the health-care system, and health education issues [1]. Relevant evidence had shown that HL is a complex issue, and low HL can increase an individual's health status, health outcomes, and the risk of misinterpreting treatment instructions [2,3]. The World Health Organization (WHO) defines HL as follows: "health literacy implies the achievement of a level of knowledge, personal skills and confidence to take action to improve personal and community health by changing personal lifestyles and living conditions".…”
Section: Introductionmentioning
confidence: 99%
“…Improved sensitivity of service organization and clinicians can enhance the quality of patient-health provider communication and improve access to health care services. This leads to a health service organization better placed to provide patient education and management that will help to improve patient ability and health outcomes associated with successfully adhered to recommended clinical care [2,4]. The concept of HL as an "asset" has evolved from roots in public health, health promotion, health education and communication.…”
Section: Introductionmentioning
confidence: 99%
“…Cost is the main attribute of the OHL because of its effect on conveying information about health plans and health care bills, (such as co-payments, out-of-pocket expenses), and health insurance [ 3 ]. Amongst the four tools (AHRQ, OHLO, HLHO-10, and Org-HLR) cost is also considered as one of the attributes of an OHL [ 15 ]. The cost includes two sub-categories ‘information about costs’ and ‘the provision of necessary funds for HL activities in the organization’.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown HL activities should be considered in the health care organization structure [ 13 , 14 , 15 ]. Organizational Health Literacy (OHL) are organizations that “facilitate the guidance, understanding, and use of information and services for health care” [ 16 ].…”
Section: Introductionmentioning
confidence: 99%